Quasiplanar Heterojunction All‐Polymer Solar Cells: A Dual Approach to Stability. (4th May 2022) - Cao, Congcong; Wang, Hengtao; Qiu, Dongsheng; Zhao, Tingxing; Zhu, Yulin; Lai, Xue; Pu, Mingrui; Li, Yan; Li, Heng; Chen, Hui; He, Feng
Abstract: In addition to efficiency, stability is another key factor in developing organic solar cells. The quasiplanar heterojunction (Q‐PHJ) structure, combining two pure layers as major and tiny nanoscale bulk heterojunction (BHJ) at interface, demonstrates superior device stability compared with BHJ devices. In this contribution, the polymer donor, PBQx‐H‐TF, and configurationally defined polymeric acceptor, PBTIC‐γ‐TSe are synthesized and used to fabricate bilayer devices by orthogonal solvents, the corresponding Q‐PHJ all‐polymer solar cells (all‐PSCs) deliver reliable stability with high efficiency. An encouraging PCE of 15.77% is achieved, which is the highest one among Q‐PHJ all‐PSCs with real‐bilayer structure. There is a major improvement over the 13.91% PCE in the BHJ device, and the carrier transport performance is improved substantially following the reduction of recombination in the Q‐PHJ all‐PSCs. Benefiting from the bilayer morphology, the stability of Q‐PHJ all‐PSCs has been greatly enhanced over that of the BHJ devices. The charge recombination process is also more serious in the aging BHJ compared with the aging Q‐PHJ all‐PSCs. This work inspires the application of Q‐PHJ in the preparation of high‐efficient all‐PSCs, but also provides guidance on the improvement of device stability from a dual approach of material and device engineering aspects. Abstract : A quasiplanar heterojunction (Q‐PHJ) structure has been utilized in the preparation of all‐polymer solar cells (all‐PSCs), and realizing the first Q‐PHJ all‐PSCs. These all‐PSCs have a stable bilayer structure and deliver the highest PCE of 15.77%. The relationships between device stability and morphology, and charge recombination have been studied and analyzed.